2018
DOI: 10.21649/akemu.v23i4.2234
|View full text |Cite
|
Sign up to set email alerts
|

Violence against Women with Disabilities: A Qualitative Investigation

Abstract: Many of the research studies have shown that usually people with disabilities and specifically women with disabilities are at increased risk of physical, sexual, and emotional abuse as well as to other practices of violence, such as institutional violence, drug use, undesirable sterilisation, medical abuse, mortification,and nuisance. This study is intended to explore the lived experiences of women with disabilities who have been subjected to any type of violence, generate a theoretical model for the ways in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Estos hallazgos se confirman también por los resultados obtenidos por Rhoda Olkin et al (2019), que exploraron la experiencia de microagresiones perpetradas hacia mujeres con discapacidades visibles e invisibles. Dentro de los estudios sociales de la discapacidad es cada vez más frecuente la literatura que considera la perspectiva de género, al entenderlo como factor fundamental en la comprensión del funcionamiento de diversos y simultáneos ejes de opresión que operan (Ashraf et al, 2018;Candela y Mulet, 2018;Harris y Wideman, 1988;Hill Collins y Bilge, 2019;Hooks, 1990;Olkin et al, 2019;Palombi, 2012;Platero y Guzmán, 2014;Purdie-Vaughns y Eibach, 2008;Schaff, 2017;Singleton, 2013;Stein y Plummer, 1994;Sue, 2010). Las mujeres con discapacidad sufren situaciones específicas relacionadas con los roles sociales asignados al género, ya sea por un efecto hiperbólico de éstos o por representar una ruptura que amplifica las situaciones de discriminación.…”
Section: Hacia Una Propuesta Operativaunclassified
“…Estos hallazgos se confirman también por los resultados obtenidos por Rhoda Olkin et al (2019), que exploraron la experiencia de microagresiones perpetradas hacia mujeres con discapacidades visibles e invisibles. Dentro de los estudios sociales de la discapacidad es cada vez más frecuente la literatura que considera la perspectiva de género, al entenderlo como factor fundamental en la comprensión del funcionamiento de diversos y simultáneos ejes de opresión que operan (Ashraf et al, 2018;Candela y Mulet, 2018;Harris y Wideman, 1988;Hill Collins y Bilge, 2019;Hooks, 1990;Olkin et al, 2019;Palombi, 2012;Platero y Guzmán, 2014;Purdie-Vaughns y Eibach, 2008;Schaff, 2017;Singleton, 2013;Stein y Plummer, 1994;Sue, 2010). Las mujeres con discapacidad sufren situaciones específicas relacionadas con los roles sociales asignados al género, ya sea por un efecto hiperbólico de éstos o por representar una ruptura que amplifica las situaciones de discriminación.…”
Section: Hacia Una Propuesta Operativaunclassified
“…Much of the research to‐date about violence experienced by people with disabilities has focused on physical and sexual violence (Ashraf et al, 2017; Dembo et al, 2018; Kouanda et al, 2022), but verbal violence has also received some attention as well. Verbal violence refers to being yelled or sworn at, being verbally humiliated, intimidated, mocked, or threatened, and being called names, all of which can cause significant psychological problems and, in some ways, has been considered as harmful or even more harmful than physical violence (Teicher et al, 2006; Uzun, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Verbal violence refers to being yelled or sworn at, being verbally humiliated, intimidated, mocked, or threatened, and being called names, all of which can cause significant psychological problems and, in some ways, has been considered as harmful or even more harmful than physical violence (Teicher et al, 2006; Uzun, 2003). Studies have examined the experience of verbal violence among many disability populations (Ashraf et al, 2017; Karni‐Vizer & Salzer, 2016; Lindsay et al, 2010; Marín‐Navarrete et al, 2022). For example, Karni‐Vizer and Salzer (2016) found that among a sample of individuals with severe mental illnesses ( N = 50) that 66% reported a verbal violence incident in the last year.…”
Section: Introductionmentioning
confidence: 99%